2022
DOI: 10.1080/21655979.2022.2079254
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α10 regulates adhesion, migration, and osteogenic differentiation of alveolar bone marrow mesenchymal stem cells in type 2 diabetic patients who underwent dental implant surgery

Abstract: Type 2 diabetes mellitus (T2DM) is a clinically important risk factor for dental implant treatment failure. An imbalance in the microenvironment of the jawbone of diabetic patients can impair the functions of bone marrow mesenchymal stem cells (BMSCs), thereby interfering with implant osseointegration during the healing phase. This study aims to investigate potential molecular factors associated with abnormal BMSC biological functions in diabetic patients with dental implant failure and identify intervention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
1
7
2
Order By: Relevance
“…Higher ALP staining intensity was observed in cultures of ND vs. D BM-MSCs ( Figure 3 ), which agrees with the work of Sun et al [ 26 ] and Liang et al [ 43 ], who reported lower ALP staining and activity in cultures of alveolar bone BM-MSCs isolated from D vs. ND donors. Thus, D BM-MSCs potentially show lower levels of ALP activity despite variation in the anatomical source.…”
Section: Discussionsupporting
confidence: 91%
“…Higher ALP staining intensity was observed in cultures of ND vs. D BM-MSCs ( Figure 3 ), which agrees with the work of Sun et al [ 26 ] and Liang et al [ 43 ], who reported lower ALP staining and activity in cultures of alveolar bone BM-MSCs isolated from D vs. ND donors. Thus, D BM-MSCs potentially show lower levels of ALP activity despite variation in the anatomical source.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis was utilized to investigate the signalling pathways that may be impacted by AC018926.2 . Figure 5C shows the top 10 enriched signalling pathways, among which the focal adhesion and phosphatidylinositol 3‐kinase (PI3K)/AKT signalling pathways, which are closely related to cell osteogenesis, were significantly downregulated in the si‐ AC018926.2 group and identified 39,40 . Therefore, we hypothesized that silence of AC018926.2 could inhibit the osteogenic process of PDLSCs by inactivating the FAK/PI3K/AKT signalling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…From the results of RNA sequencing and KEGG analysis, we found that the FAK and PI3K/AKT pathway were significantly downregulated following AC018926.2 knockdown (Figure 5C). Previous studies have shown that activation of the FAK/PI3K/AKT pathway is positively associated with cell osteogenic differentiation 39,40 . As an important member of the integrin family, ITGA2 has been reported to enhance the osteogenic capacity of cells by activating the FAK signalling pathway 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Yu-Hua Pan et al, also showed in a comparison between control and GDP-treated zirconia disks that increased surface roughness is associated with higher contact angle ( Pan et al, 2020 ). In the current study, the major objective was functionalization with fibronectin proteins to enhance osteoblastic-like cell adhesion and proliferation ( Chang et al, 2016b ; Liang et al, 2022 ) in combination with improved physical properties of surface roughness and wettability of zirconia ceramic.…”
Section: Discussionmentioning
confidence: 99%